PERANAN PENYULUH PERIKANAN UNTUK MENINGKATKAN PRODUKSI DAN PENDAPATAN PEMBUDIDAYA TAMBAK DI KABUPATEN SINJAI - jumain -; Hadijah -; Sri Mulyani (Postgraduate Bosowa University Publishing, 2018)
This study aims to analyze the contribution of instruction towards income and fishers production increase. Also to analyze the variables which influenced by the increase of the income and fishers production in Sinjai District. This research was conducted in Sinjai District for 3 months long from December 2015 to February 2016. This study was designed using a combination of quantitative method with editing proccess and multiple linear regression analysis with tables. The result showed that instruction does effecting the increase of income and fishers production, and also effecting the education variable, farmer experience, connection with instructor, the amount of family burden, land area, and farming cost with positive contribution. The variable of farmers’ life span showed a negative contribution towards income and production which indicated that most of farmers categorized as unproductive labours.